2014
DOI: 10.2147/ijwh.s72075
|View full text |Cite
|
Sign up to set email alerts
|

Scientific research in obstetrics and gynecology: changes in the trends over three decades

Abstract: AimThe aim of this work was to assess scientific research of master’s and doctoral theses and essays in the Department of Obstetrics and Gynecology, Zagazig University, Egypt.Materials and methodsAll master’s and doctoral theses and essays since the foundation of Department of Obstetrics and Gynecology, Zagazig University, Egypt, in 1975 till end of 2012 were reviewed.ResultsA total of 703 theses and essays were reviewed. The important topics in the specialty of obstetrics and gynecology were covered and updat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In India, till now most of the training facilities and programs are not able to institute proper measures to support resident research activities during COVID-19 pandemic. [12][13][14][15] This cross-sectional study aimed to evaluate the impact of the COVID-19 pandemic on the research in OBG residency training program in a government medical college of India. Findings from the study showed that among OBG residents, COVID-19 pandemic was associated with a significant research training impairment.…”
Section: Discussionmentioning
confidence: 99%
“…In India, till now most of the training facilities and programs are not able to institute proper measures to support resident research activities during COVID-19 pandemic. [12][13][14][15] This cross-sectional study aimed to evaluate the impact of the COVID-19 pandemic on the research in OBG residency training program in a government medical college of India. Findings from the study showed that among OBG residents, COVID-19 pandemic was associated with a significant research training impairment.…”
Section: Discussionmentioning
confidence: 99%